The influence of diabetic status on the pharmacokinetics of clopidogrel and its metabolites in patients suffered from cardiovascular diseases - Karaźniewicz-Łada, Marta; Danielak, Dorota; Burchardt, Paweł; Główka, Franciszek (Journal of Medical Science, 2014)
Aim. A significant percentage of individuals treated with an anti-platelet agent clopidogrel do not receive the expected therapeutic effect. Clopidogrel resistance is even more prevalent in patients with type 2 diabetes mellitus (DM). An extensive investigation on pharmacokinetics of clopidogrel and its metabolites in patients with type 2 DM suffering from cardiovascular diseases were performed following an administration of 75 mg of the drug. Material and methods. Plasma concentrations of clopidogrel, its carboxylic metabolite (CLPM) and diastereoisomers of a thiol metabolite (the inactive H3 and the active H4) were determined by a validated HPLC-MS/MS method. The pharmacokinetic parameters of the analytes in diabetic (n = 16) and non-diabetic (n = 28) patients were compared and correlated with platelet aggregation. Results. DM patients exhibited a slightly higher Cmax of clopidogrel (2.34 ± 2.29 ng/mL) compared with non-diabetic group (1.82 ± 1.86 ng/mL), whereas plasma levels of clopidogrel metabolites were lower in DM than in non-DM patients (2339 ± 989 ng/mL vs. 2662 ± 2090 ng/mL, 4.64 ± 4.79 ng/mL vs. 5.42 ± 4.55 ng/mL and 6.42 ± 4.80 ng/mL vs. 7.44 ± 7.18 ng/mL, respectively for CLPM, H3 and H4). A significant correlation was found between platelet aggregation and the Cmax of the active H4 metabolite in non-diabetic patients. Conclusions. Pharmacokinetic parameters of clopidogrel, CLPM, H3 and H4 isomers in patients with DM did not differ significantly from those determined in non-diabetic group. Moreover, the antiplatelet response to clopidogrel therapy measured by ADP-stimulated platelet aggregation was similar in both groups of patients.